Design of Website-Based SPP Payment System Using Payment Gateway Midtrans on PAUD At-Taqwa - Muhammad Fadel Hasan Maliki; Umar Mansyuri; Rahadian Arief (Brilliance: Research of Artificial Intelligence, 2025)
PAUD At-Taqwa still uses a manual tuition payment (SPP) system, where parents must come directly to the school to make payments, and transaction records are on physical cards. This method is prone to errors, delays in reporting, and lacks accessibility. In response to these issues, this study aims to design and develop a web-based SPP payment system integrated with the Midtrans payment gateway to support both online and offline transactions. This system was developed using Laravel framework, which supports structured development and efficient web application handling. The objective is to provide a more affective and efficient payment process for both parents and administrators. The method used in this research involved analyzing the current system using the SWOT analysis approach to identify strengths, weaknesses, opportunities, and threats, which then served as the fondation for system development. The system was tested using Black Box Testing to ensure all functions worked as expected. The final product allows parents to view bills, make payment online or offline, and access digital payment receipts, while administrators can manage student data, generate bills, and view real-time reports. The results indicate that the proposed system successfully improves the efficiency and accuracy of the SPP payment process at PAUD At-Taqwa. Futher development such as mobile support could enchance the system’s accessibility in the future.